A Method for the Transformation of Abandoned Coal Mine Clusters and the Coordination Planning of Cultural Tourism Resources - Haoyu Tao; Xiaodan Li; Zhen Liu; Zhiping Liu; Jing Li; Yangyang Wang (Land)
To promote the economic revitalization and cultural prosperity of abandoned coal mine clusters and facilitate regional sustainable development, this study involved the construction of a ranking system for coal mines suitable for cultural tourism transformation and a regional cultural tourism resource coordination planning framework. The research findings and innovations are as follows: (1) Through a combination of subjective judgment and quantitative analysis, an AHP–entropy–TOPSIS evaluation model for the transformation of abandoned coal mine clusters was developed. This model significantly enhances the scientific and precise nature of the decision-making process. (2) By integrating cultural tourism land use indicators, a ranking system for the suitability of coal mines for transformation into cultural tourism destinations was established, enabling the identification of the most suitable coal mines for transformation. (3) The most suitable coal mines for transformation were then integrated with regional historical cultural resources. An innovative application of circuit theory was used to optimize the regional road network, while a kernel density analysis was employed to perform the functional zoning of the study area. This resulted in a comprehensive regional cultural tourism resource coordination planning framework. This study offers a valuable reference for transforming abandoned coal mines and integrating cultural tourism, contributing to regional sustainable development.